Case Report: Association of a Variant of Unknown Significance in the FIG4 Gene With Frontotemporal Dementia and Slowly Progressing Motoneuron Disease: A Case Report Depicting Common Challenges in Clinical and Genetic Diagnostics of Rare Neuropsychiatric and Neurologic Disorders - Bergner, Caroline Gertrud; Neuhofer, Christiane Michaela; Funke, Claudia; Biskup, Saskia; von Gottberg, Philipp; Bartels, Claudia; Koch, Jan Christoph; Radenbach, Katrin (Frontiers in Neuroscience, 2020)
Background Modern genetics have in many ways revolutionized clinical routine and have for instance shown that formerly distinct disease entities relate to common pathogenic mutations. One such example is the connection between dementia and amyotrophic lateral sclerosis in a continuous disease spectrum affirmed by the discovery of shared mutations. Case report We describe a new variant in the FIG4 gene in a patient with slowly progressing frontotemporal dementia (FTD) and probable primary lateral sclerosis (PLS). The patient initially showed depressive symptoms and global cognitive deficits, including severe difficulties with language, associated with hallucinations became clear as the disease progressed. Nuclear medicine imaging and CSF biomarkers were not specific for defined categories of dementia, but neuropsychological testing and clinical features finally led to an allocation of the syndrome to the non-fluent variant of primary progressive aphasia (nfv PPA). Due to increasing limb weakness and bulbar symptoms motoneuron disease in form of PLS was diagnosed, strongly supported by elevated CSF neurofilament and electrophysiologic assessments. The detected variant in the FIG4-gene, is described as pathogenic or likely pathogenic in common databases and reported once in the literature. While the phenotype of our patient fits the description of FIG4-associated disease in literature, we consider the present variant as VUS in this case. Conclusion We describe a variant in the FIG 4 gene in a patient with slowly progressing FTD and PLS. Mutations in the FIG4 gene have been associated with amyotrophic lateral sclerosis (ALS) and PLS, however this exact mutation was not reported in ALS or PLS patients before. The case illustrates generic diagnostic challenges in patients presenting with genetic variants that offer an explanation for otherwise uncommon symptom combinations but yet are of unknown significance.